Beispiel Nr: 42
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y= 4x^2-2x-3\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y= 4x^2-2x-3\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=4x^2-2x-3 \\ y=4(x^2-\frac{1}{2}x-\frac{3}{4}) \\ y=4(x^2-\frac{1}{2}x+\left(\frac{1}{4}\right)^2-\left(\frac{1}{4}\right)^2-\frac{3}{4}) \\ y=4[(x-\frac{1}{4})^2-\left(\frac{1}{4}\right)^2-\frac{3}{4}] \\ y=4[(x-\frac{1}{4})^2-\frac{1}{16}-\frac{3}{4}] \\ y=4[(x-\frac{1}{4})^2-\frac{13}{16}] \\ y=4(x-\frac{1}{4})^2-3\frac{1}{4} \\ Scheitel(\frac{1}{4}/-3\frac{1}{4}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=4x^2-2x-3 \\ y=4(x^2-\frac{1}{2}x)-3 \\ y=4(x^2-\frac{1}{2}x+\left(\frac{1}{4}\right)^2-\left(\frac{1}{4}\right)^2)-3 \\ y=4[(x-\frac{1}{4})^2-\left(\frac{1}{4}\right)^2]-3 \\ y=4[(x-\frac{1}{4})^2-\frac{1}{16}]-3 \\ y=4(x-\frac{1}{4})^2-\frac{1}{4}-3 \\ y=4(x-\frac{1}{4})^2-3\frac{1}{4} \\ Scheitel(\frac{1}{4}/-3\frac{1}{4}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=4x^2-2x-3 \\ xs=-\frac{-2}{2\cdot 4} \\ xs=\frac{1}{4} \\ ys=-3-\frac{\left(-2\right)^2}{4\cdot4} \\ ys=-3\frac{1}{4} \\ Scheitel(\frac{1}{4}/-3\frac{1}{4})\\ y=4(x-\frac{1}{4})^2-3\frac{1}{4} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = [(-3\frac{1}{4});\infty[ \\ \\=4(x+0,651)(x-1,15)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y= 4x^2-2x-3 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 4x^{2}-2x-3 =0 \\ x_{1/2}=\displaystyle\frac{+2 \pm\sqrt{\left(-2\right)^{2}-4\cdot 4 \cdot \left(-3\right)}}{2\cdot4} \\ x_{1/2}=\displaystyle \frac{+2 \pm\sqrt{52}}{8} \\ x_{1/2}=\displaystyle \frac{2 \pm7,21}{8} \\ x_{1}=\displaystyle \frac{2 +7,21}{8} \qquad x_{2}=\displaystyle \frac{2 -7,21}{8} \\ x_{1}=1,15 \qquad x_{2}=-0,651 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ 4x^{2}-2x-3 =0 \qquad /:4 \\ x^{2}-\frac{1}{2}x-\frac{3}{4} =0 \\ x_{1/2}=\displaystyle -\frac{-\frac{1}{2}}{2}\pm\sqrt{\left(\frac{\left(-\frac{1}{2}\right)}{2}\right)^2- \left(-\frac{3}{4}\right)} \\ x_{1/2}=\displaystyle \frac{1}{4}\pm\sqrt{\frac{13}{16}} \\ x_{1/2}=\displaystyle \frac{1}{4}\pm0,901 \\ x_{1}=1,15 \qquad x_{2}=-0,651 \end{array}\\ \end{array}\\ \underline{x_1=-0,651; \quad1\text{-fache Nullstelle}} \\\underline{x_2=1,15; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-0,651&< x <&1,15&< x\\ \hline f(x)&+&0&-&0&+\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-\infty;-0,651[\quad \cup \quad]1,15;\infty[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-0,651;1,15[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$